A Role of a Newly Identified Isomerase From Yarrowia lipolytica in Erythritol Catabolism - Mirończuk, Aleksandra M.; Biegalska, Anna; Zugaj, Karolina; Rzechonek, Dorota A.; Dobrowolski, Adam (Frontiers in Microbiology, 2018)
Erythritol is a natural sweetener produced by microorganisms as an osmoprotectant. It belongs to the group of polyols and it can be utilized by the oleaginous yeast Yarrowia lipolytica. Despite the recent identification of the transcription factor of erythritol utilization (EUF1), the metabolic pathway of erythritol catabolism remains unknown. In this study we identified a new gene, YALI0F01628g, involved in erythritol assimilation. In silico analysis showed that YALI0F01628g is a putative isomerase and it is localized in the same region as EUF1. qRT-PCR analysis of Y. lipolytica showed a significant increase in YALI0F01628g expression during growth on erythritol and after overexpression of EUF1. Moreover, the deletion strain ΔF01628 showed significantly impaired erythritol assimilation, whereas synthesis of erythritol remained unchanged. The results showed that YALI0F1628g is involved in erythritol assimilation; thus we named the gene EYI1. Moreover, we suggest the metabolic pathway of erythritol assimilation in yeast Y. lipolytica.